Modelling human embryogenesis: embryo-like structures spark ethical and policy debate - Pereira Daoud, Ana M; Popovic, Mina; Dondorp, Wybo J; Trani Bustos, Marc; Bredenoord, Annelien L; Chuva de Sousa Lopes, Susana M; van den Brink, Susanne C; Roelen, Bernard A J; de Wert, Guido M W R; Heindryckx, Björn (Human reproduction update, 2020)
Studying the human peri-implantation period remains hindered by the limited accessibility of the in vivo environment and scarcity of research material. As such, continuing efforts have been directed towards developing embryo-like structures (ELS) from pluripotent stem cells (PSCs) that recapitulate aspects of embryogenesis in vitro. While the creation of such models offers immense potential for studying fundamental processes in both pre- and early post-implantation development, it also proves ethically contentious due to wide-ranging views on the moral and legal reverence due to human embryos. Lack of clarity on how to qualify and regulate research with ELS thus presents a challenge in that it may either limit this new field of research without valid grounds or allow it to develop without policies that reflect justified ethical concerns. The aim of this article is to provide a comprehensive overview of the existing scientific approaches to generate ELS from mouse and human PSCs, as well as discuss future strategies towards innovation in the context of human development. Concurrently, we aim to set the agenda for the ethical and policy issues surrounding research on human ELS. The PubMed database was used to search peer-reviewed articles and reviews using the following terms: 'stem cells', 'pluripotency', 'implantation', 'preimplantation', 'post-implantation', 'blastocyst', 'embryoid bodies', 'synthetic embryos', 'embryo models', 'self-assembly', 'human embryo-like structures', 'artificial embryos' in combination with other keywords related to the subject area. The PubMed and Web of Science databases were also used to systematically search publications on the ethics of ELS and human embryo research by using the aforementioned keywords in combination with 'ethics', 'law', 'regulation' and equivalent terms. All relevant publications until December 2019 were critically evaluated and discussed. In vitro systems provide a promising way forward for uncovering early human development. Current platforms utilize PSCs in both two- and three-dimensional settings to mimic various early developmental stages, including epiblast, trophoblast and amniotic cavity formation, in addition to axis development and gastrulation. Nevertheless, much hinges on the term 'embryo-like'. Extension of traditional embryo frameworks to research with ELS reveals that (i) current embryo definitions require reconsideration, (ii) cellular convertibility challenges the attribution of moral standing on the basis of 'active potentiality' and (iii) meaningful application of embryo protective directives will require rethinking of the 14-day culture limit and moral weight attributed to (non-)viability. Many conceptual and normative (dis)similarities between ELS and embryos thus remain to be thoroughly elucidated. Modelling embryogenesis holds vast potential for both human developmental biology and understanding various etiologies associated with infertility. To date, ELS have been shown to recapitulate several aspects of peri-implantation development, but critically, cannot develop into a fetus. Yet, concurrent to scientific innovation, considering the extent to which the use of ELS may raise moral concerns typical of human embryo research remains paramount. This will be crucial for harnessing the potential of ELS as a valuable research tool, whilst remaining within a robust moral and legal framework of professionally acceptable practices.